Land Reform in Kenya: The History of an Idea (Strathmore Law Journal, 2021)
The great legal scholar Patrick McAuslan described the 1990s as inaugurating a new era of land law reform. Land law reform has taken place on a significant scale since 1990: a total of 32 new national land laws have been enacted since 1990 in nearly 60 per cent of African states. Land issues have been the cause of both simmering discontent and violent conflict throughout Kenya’s colonial and post-colonial history. They remain a ‘key fault line’ in modern Kenya. Historians of Kenya and commentators on its politics continue to find patrimonialism, ethnic favouritism and corruption at play, nowhere more so than in the politics of land. Kenya’s problems with land defy easy description: they remain complex and multi-faceted and include massive and worsening inequalities in access to land, a propensity to land grabbing and continuing conflicts over who is and who is not entitled to occupy land. Efforts to address these problems have since before independence been erratic at best.